2015
DOI: 10.1007/s00464-015-4314-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized and controlled study of mesh displacement after laparoscopic inguinal repair: fixation versus no fixation of mesh

Abstract: Fixation of the mesh for TEP repair is unnecessary. TEP repair with no mesh fixation is safe and is not associated with increased risk of mesh displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 42 publications
4
52
0
Order By: Relevance
“…Claus et al investigated mesh migration in laparoscopic TEP hernia repair and compared results of radiological examinations performed immediately, and 30 days after surgery in groups that underwent hernia repair with or without mesh fixation, and also reported lack of any difference between groups. [19] In their meta-analysis, Tam et al reported that hernia repair using TEP laparoscopic method without mesh fixation could significantly decrease operative time, surgical costs, and length of hospital stay, and they found no difference between mesh fixation and nonfixation methods in terms of hernia recurrence, complications, or postoperative pain. [20] In another meta-analysis performed by Sajid et al, authors indicated that laparoscopic nonfixation TEP method did not increase recurrence risk, and indicated that operative time, postoperative pain, complications, length of hospital stay, and chronic inguinal pain were similar to that detected in cases of mesh fixation method.…”
Section: Discussionmentioning
confidence: 99%
“…Claus et al investigated mesh migration in laparoscopic TEP hernia repair and compared results of radiological examinations performed immediately, and 30 days after surgery in groups that underwent hernia repair with or without mesh fixation, and also reported lack of any difference between groups. [19] In their meta-analysis, Tam et al reported that hernia repair using TEP laparoscopic method without mesh fixation could significantly decrease operative time, surgical costs, and length of hospital stay, and they found no difference between mesh fixation and nonfixation methods in terms of hernia recurrence, complications, or postoperative pain. [20] In another meta-analysis performed by Sajid et al, authors indicated that laparoscopic nonfixation TEP method did not increase recurrence risk, and indicated that operative time, postoperative pain, complications, length of hospital stay, and chronic inguinal pain were similar to that detected in cases of mesh fixation method.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies examined by Tam et al had a median follow‐up period of less than 12 months. Several other trials similarly found that there was no significant difference between having and not having fixation in terms of short‐term to midterm recurrence . Long‐term results are insufficient to draw further conclusions.…”
Section: Discussionmentioning
confidence: 95%
“…Studies on recurrence after laparoscopic repair have attributed it to improper fixation and mesh migration, and as a result, mesh fixation with various devices has become a widespread practice . However, in recent years, encouraging early results have bolstered the concept of non‐fixation, but the long‐term benefits are unclear if mesh migration occurs; moreover, current data are insufficient to support its widespread use …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 One recurrence has thus far been detected after six months (0.2%). This was confirmed by laparoscopy to be a lateral recurrence associated with infolded mesh in a patient in the mesh fixation group, and re-repaired using a laparoscopic transabdominal approach (a 2 cm indirect defect had been repaired with mesh fixated by eight tacks).…”
Section: Discussionmentioning
confidence: 98%